A novel evaluation methodology for dimension stone quality - Strzałkowski, Paweł; Köken, Ekin (Wydział Geoinżynierii, Górnictwa i Geologii Politechniki Wrocławskiej, 2024)
The physical and mechanical properties of natural stones are crucial factors in determining their quality, predicting their durability, and assessing their potential uses. In this study, a novel method is introduced to assess the quality of dimension stone using the Fuzzy logic inference system (FIS). The FIS analysis results are described as dimension stone field performance coefficient (DSFPC), which indicates the quality of dimension stones. The analysis results are also compared with different approaches, and it is concluded that the proposed FIS model can reliably be used to quantify the quality of dimension stones. The present study, in this manner, contributes to the natural stone industry by proposing a comprehensive predictive model used to quantify the dimension stone quality based on critical physicomechanical rock properties.
Mining Science, Vol. 31, 2024, s. 119-143
Keywords: górnictwo; geologia; geoinżynieria; fuzzy logic inference system; rock properties; dimension stone quality; soft computing